PMN J1310–5552: A Gamma-Ray-emitting Blazar Candidate Harboring a Cosmic Monster - Vaidehi S. Paliya (The Astrophysical Journal)
Relativistic jets manifest some of the most intriguing activities in the nuclear regions of active galaxies. Identifying the most powerful relativistic jets permits us to probe the most luminous accretion systems and, in turn, the most massive black holes. This paper reports the identification of one such object, PMN J1310−5552 ( z = 1.56), a blazar candidate of uncertain type detected with the Fermi Large Area Telescope (LAT) and Swift Burst Alert Telescope. The detection of broad emission lines in its optical spectra taken with the X-Shooter and Goodman spectrographs classifies it to be a flat-spectrum radio quasar. The analysis of the Goodman optical spectrum has revealed PMN J1310−5552 harbors a massive black hole (log scale M _BH = 9.90 ± 0.07, in M _⊙ ) and luminous accretion disk (log scale L _disk = 46.86 ± 0.03, in erg s ^−1 ). The fitting of the observed big blue bump with the standard accretion disk model resulted in the log scale M _BH $\,=\,{9.81}_{-0.20}^{+0.19}$ (in M _⊙ ) and L _disk $\,=\,{46.86}_{-0.09}^{+0.09}$ (in erg s ^−1 ), respectively. These parameters suggest PMN J1310−5552 hosts one of the most massive black holes and the most luminous accretion disks among the blazar population. The physical properties of this enigmatic blazar were studied by modeling the broadband spectral energy distribution considering the data from NuSTAR, Swift, Fermi-LAT, and archival observations. Overall, PMN J1310−5552 is a powerful “MeV” blazar with physical parameters similar to other members of this unique class of blazars. These results provide glimpses of monsters lurking among the unknown high-energy emitters and demonstrate the importance of ongoing wide-field sky surveys to discover them.